2005
DOI: 10.1161/01.cir.0000160924.73417.26
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count Predicts Reduction in Coronary Heart Disease Mortality With Pravastatin

Abstract: Background-Elevated serum inflammatory marker levels are associated with a greater long-term risk of cardiovascular events. Because 3-hydroxy-3-methylglutaryl coenzyme-A reductase inhibitors (statins) may have an antiinflammatory action, it has been suggested that patients with elevated inflammatory marker levels may have a greater reduction in cardiovascular risk with statin treatment. Methods and Results-We evaluated the association between the white blood cell count (WBC) and coronary heart disease mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Blacks have previously been demonstrated to have lower WBC counts than Whites [29, 30]. We also noted that among WASID subjects, an increased baseline WBC was associated with diabetes, obesity and hypertriglyceridemia, thereby supporting the results of previous studies pointing to inflammation as part of the metabolic syndrome [18, 31]. Similar to other studies that showed no association between inflammatory markers and low-density lipoprotein cholesterol level [2, 32], we did not observe any relationship between WBC and low-density lipoprotein cholesterol in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Blacks have previously been demonstrated to have lower WBC counts than Whites [29, 30]. We also noted that among WASID subjects, an increased baseline WBC was associated with diabetes, obesity and hypertriglyceridemia, thereby supporting the results of previous studies pointing to inflammation as part of the metabolic syndrome [18, 31]. Similar to other studies that showed no association between inflammatory markers and low-density lipoprotein cholesterol level [2, 32], we did not observe any relationship between WBC and low-density lipoprotein cholesterol in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Elevated WBC and neutrophils in patient [29,30] peripheral circulation have been shown to be associated with a greater risk of cardiovascular events in many epidemiological and clinical studies [31,32]. In our study, peripheral blood WBCs are elevated 4 to 24 h after PCI in patients.…”
Section: Figure 3 Effects Of Different Doses Of 1400w (A) and Sin-1 (supporting
confidence: 53%
“…In the LIPID (Long-term Intervention with Pravastatin in Ischemic Disease) study, leucocyte count predicted cardiac mortality in patients randomized to placebo, but not in those who received pravastatin [22]. In the present study 90 % of patients with ACS received statins within the first year following PCI.…”
Section: Discussionmentioning
confidence: 46%